N‐Heteroarylation of Optically Pure α‐Amino Esters using the Pd‐PEPPSI‐IPentCl‐o‐picoline Pre‐Catalyst. Issue 42 (5th September 2016) - Sharif, Sepideh; Mitchell, David; Rodriguez, Michael J.; Farmer, Jennifer L.; Organ, Michael G.
Abstract: A robust, mild, and efficient method for the Pd‐catalyzed N‐heteroarylation of optically pure α‐amino esters was developed. Dichloro[1, 3‐bis(2, 6‐di‐3‐pentylphenyl)imidazol‐2‐ylidene]( o ‐picoline)palladium(II) (Pd‐PEPPSI‐IPent Cl ‐ o ‐picoline; PEPPSI=pyridine enhanced pre‐catalyst preparation, stabilization, and initiation) was shown to effectively couple a variety of amino acids as the tert ‐butyl ester with heteroaryl chlorides in high yields and with excellent stereoretention of the acidic proton adjacent to the ester. Control experiments revealed that racemization is base‐mediated, with no evidence of Pd‐mediated β‐hydride elimination when using Pd‐PEPPSI‐IPent Cl, and that racemization occurs only after the product is formed, that is, the non‐arylated starting amino ester does not deprotonate under our reaction conditions. Studies also revealed that increasing the steric bulk of the ester moiety on the amino acid (e.g., ethyl to tert ‐butyl) drastically slows racemization of the product. Abstract : A mild‐mannered reagent ! A robust, mild and efficient method for N‐heteroarylation of α‐amino esters using Pd‐PEPPSI‐IPent Cl ‐ o ‐picoline was developed. Using this method, a variety of N‐heteroaryl α‐amino esters were prepared in high yield with excellent enantiomeric purity.